2008
DOI: 10.3168/jds.2008-1298
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Udder Cisterns and Effects on Milk Yield of Dairy Ewes

Abstract: Nine Manchega (0.94 L/d) and 10 Lacaune (2.07 L/d) ewes at the same stage of lactation (90 d in milk) were used to study the interbreed differences in milk yield, mammary morphological traits, and machine-milking ability. Udder traits were measured after 6 h of udder filling before the start of the experiment. Cisternal area (by ultrasonography), cisternal milk (by teat cannula drainage), and alveolar milk (by machine milking after an intravenous oxytocin injection) were randomly measured 8 h after milking for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
37
5
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 19 publications
7
37
5
2
Order By: Relevance
“…No significant differences were observed between milk protein, lactose and total solid percentages of cisternal and alveolar milk during suckling and milking periods. These results agree in part with those findings in dairy ewes (Rovai et al, 2008), dairy goats (Salama et al, 2004), dairy cows and lactating dromedary camels (Ayadi et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…No significant differences were observed between milk protein, lactose and total solid percentages of cisternal and alveolar milk during suckling and milking periods. These results agree in part with those findings in dairy ewes (Rovai et al, 2008), dairy goats (Salama et al, 2004), dairy cows and lactating dromedary camels (Ayadi et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…The discrepancies in results between the latter study and our findings are probably due to their longer milking period, milking with machine and breed differences. The teat width and angle observed in the current study for Najdi ewes were smaller in values than those values reported for Manchega, Lacaune, Merino Rambouillet and Chios dairy breed ewes Ochoa-Cordero et al, 2006;Rovai et al, 2008;Gelasakis et al, 2012). Teat angle in Najdi ewes was greater than the average value observed in French Rouge de l'Ouest ewes (26.5°, Malher & Vrayla-Anesti, 1994).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Conversely, ewes with a higher machine stripping rate had higher log SCC. The level of milk production in high-yielding dairy sheep depends mainly on the capacity of their udder cisterns and greater storage of milk between milkings (Rovai et al, 2008). In that study ewes of two breeds, Manchega and Lacaune, produced approximately the same amount of alveolar milk; however, Lacaune ewes had greater volumes and larger areas of the cisterns, and greater milk yield when compared with Manchega ewes.…”
Section: Udder Morphology and Machine Milking Abilitymentioning
confidence: 82%
“…Attention is also paid to breeding for morphological characteristics of the udders in dairy sheep Rovai et al 2009;Sadeghi et al 2014).…”
Section: Sheepmentioning
confidence: 99%